Interface bonding layer of lithium and solid electrolyte, interface bonding method and application

By using magnetic sputtering technology in the solid metal lithium battery, the interface key layer of the interface key and other materials of tin lead alloys and other materials on the solid electrolyte surface is used to solve the problem of instability of solid electrolyte and metal lithium interface, which significantly improves the energy density of the battery The life expectancy enhances electrochemical properties and security.

CN119381539AActive Publication Date: 2025-01-28XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411701437.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

In solid-state metal lithium batteries, the instability of the interface between solid electrolyte and metal lithium leads to a decline in battery performance, affecting its commercial application.

Method used

Magnetic sputtering on the surface of the solid electrolyte substrate material, the key layer is deposited. The key layer is composed of tin lead alloys, tin silver -copper triple alloy and other materials to form the interface key layer, which significantly improves the interface stability of the battery.

Benefits of technology

It significantly improves the energy density and cycle life of the battery, reduces interface impedance, enhances electrochemical performance, and improves the safety and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of energy storage materials, and relates to an interface bonding layer of lithium and solid electrolyte, an interface bonding method and application, the bonding layer is deposited on the surface of a solid electrolyte matrix material through magnetron sputtering, and the bonding layer can be composed of tin-lead alloy, tin-silver-copper ternary alloy and other materials. The electrolyte is suitable for solid electrolytes of NASICON type, garnet type, sulfide, halide and the like; the bonding process is carried out at 70 DEG C under the pressure of 200MPa, so that the interface stability of the battery is remarkably improved, the interface impedance is reduced, the energy density is effectively improved, and the cycle life is effectively prolonged; in addition, the composition of the bonding layer and lithium have certain solubility, binary or multi-element alloy can be formed, uniform deposition of lithium is promoted, formation of lithium dendrites is inhibited, and the failure risk of the battery is reduced. According to the invention, the safety and stability of the battery are improved, the overall electrochemical performance is optimized, and powerful support is provided for the practical application of the solid-state metal lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy storage materials and relates to an interface bonding layer between lithium and a solid electrolyte, an interface bonding method and applications. Background Art

[0002] As an energy storage technology, solid-state metal lithium batteries have attracted widespread attention due to their high energy density, excellent safety and long cycle life. Compared with traditional liquid batteries, solid-state metal lithium batteries use solid electrolytes, which significantly reduce the risk of leakage and combustion, and solve many safety hazards of traditional batteries.

[0003] However, the commercialization of this technology still faces many challenges, among which the instability of the interface between solid electrolyte and metallic lithium is particularly critical. In solid-state lithium metal batteries, solid electrolytes usually include a variety of materials such as NASICON oxides, garnets, sulfides and halides. Each solid electrolyte may have different forms of interfacial instability problems when in contact with metallic lithium. For example, (1) NASICON oxide solid electrolytes are prone to chemical reactions when in contact with lithium metal to generate non-conductive lithium compounds, thereby reducing the overall performance of the battery. In addition, the volume of lithium metal changes significantly during charging and discharging, which may induce mechanical stress and lead to the formation of interfacial cracks, further affecting ionic conductivity. (2) Garnet-type solid electrolytes are favored for their excellent ionic conductivity, but their interfacial impedance with metallic lithium is relatively high, which directly affects the battery's cycle performance and energy efficiency. Studies have found that as the temperature increases, garnet-type electrolytes may undergo phase changes with lithium metal, resulting in interfacial instability, which in turn accelerates the decline of battery performance. (3) Sulfide solid electrolytes generally have good conductivity, but they may react with lithium metal at high temperatures to form low-conductivity lithium sulfide, which affects the conductivity of the battery. In addition, the corrosion problem of lithium metal at the sulfide electrolyte interface needs to be solved urgently. This corrosion not only leads to interface degradation, but also may cause battery cycle instability. (4) Halide solid electrolytes, such as chlorides and iodides, also face the problem of chemical instability when in contact with metallic lithium. They may react with lithium metal during battery operation to form non-conductive byproducts, affecting the efficiency of ion migration. At the same time, the deposition and stripping process of lithium in the halide electrolyte may also lead to non-uniform distribution of lithium, further affecting the performance of the battery.

[0004] Therefore, solid-state lithium metal batteries have great development potential, but their interface instability problem is still a bottleneck restricting their commercial application. In-depth research on the interface interaction between solid electrolytes and lithium metal will pave the way for the future development of solid-state batteries and achieve high-performance, safe and reliable energy storage solutions. Summary of the invention

[0005] The present invention aims at the problem of instability of the interface between solid electrolyte and metal lithium faced by solid metal lithium batteries, and provides a universal method for bonding the interface between metal lithium and solid electrolyte and the application of solid lithium batteries, including depositing a bonding layer on the surface of a solid electrolyte matrix material by magnetron sputtering, wherein the bonding layer is composed of materials such as tin-lead alloy, tin-silver-copper ternary alloy, etc. The solid electrolyte can be NASICON type, garnet type, sulfide or halide. The bonding process is carried out at 70°C and 200MPa pressure, and is suitable for the preparation of solid-state lithium symmetrical batteries or solid-state lithium metal full batteries. The method is universal, and the method significantly improves the interface stability of the battery, reduces the interface impedance, and thus effectively improves the energy density and cycle life of the battery. In addition, the modification and enhancement technology of the interface bonding layer further optimizes the ionic conductivity of the battery, improves the overall electrochemical performance, and makes the solid-state metal lithium battery have better safety and high efficiency.

[0006] The technical solution adopted by the present invention to solve the technical problem is: an interface bonding layer between lithium and a solid electrolyte, wherein the interface bonding layer is a bonding layer formed by depositing a bonding layer alloy on the surface of a solid electrolyte matrix material by radio frequency magnetic sputtering; the bonding layer alloy includes: tin-lead alloy, tin-silver-copper ternary alloy, tin-silver alloy, tin-copper alloy, and Wood's alloy; the solid electrolyte includes: NASICON type oxide solid electrolyte, garnet type solid electrolyte, sulfide solid electrolyte, and halide solid electrolyte; the interface bonding layer is a bonding layer formed by depositing a bonding layer alloy on one side or both sides of the solid electrolyte matrix material by radio frequency magnetic sputtering. The components in the bonding layer have a certain solubility with lithium and can form a binary or multi-element alloy with lithium. This alloy can not only effectively bond the solid electrolyte to the metal lithium negative electrode, improve the interface physical contact behavior between the solid electrolyte and the metal lithium negative electrode, but also induce the nuclear growth of metal lithium by adjusting the interface characteristics, and promote its uniform deposition. This process helps to inhibit the formation of lithium dendrites, thereby reducing the risk of damage and failure caused by lithium dendrites to the solid electrolyte. Through this optimized interface bonding technology, not only the safety and stability of the battery are improved, but also its electrochemical performance is enhanced and the cycle life is extended.

[0007] The thickness of the interface bonding layer is 0.5 to 5 μm. The thickness of the interface modification layer will affect the battery performance. An overly thick interface modification layer will increase the impedance of the interface, that is, increase the transmission resistance of lithium ions. An overly thin interface modification layer is easily damaged and failed during the charge and discharge process of the battery. Therefore, it is necessary to take both of the above into consideration and select the optimal thickness.

[0008] Preferably, the NASICON type solid electrolyte comprises: Li 1+x Al x Ti 2-x (PO4)3(x=0.3~0.5) and Li1+x Al x Ge 2-x (PO4)3(x=0.3~0.5); garnet-type solid electrolytes include: Li7La3Zr2O 12 , Li 3+x La 2 / 3- x TiO3, Li5La3Nb2O 12 and Li 6.25 LqCy 1.75 Ta 0.25 O 12 ; Sulfide solid electrolytes include: Li2S-P2S5, Li 10 GeP2S 12 ,Li7P3S 11 and Li2S-Sb2S3; halide solid electrolytes include: Li3MX6 (M=Y, Er, Sc, In, X=F, Cl, Br) and Li2MCl6 (M=Zr, Cd, Ti).

[0009] More preferably, the combination of the interface bonding layer includes: Li 1+x Al x Ti 2-x (PO4)3 solid electrolyte and tin-lead alloy bonding layer combination, Li7La3Zr2O 12 Combination of solid electrolyte and tin-silver-copper ternary alloy bonding layer, combination of Li2S-P2S5 solid electrolyte and tin-lead alloy bonding layer, combination of Li3MX6 solid electrolyte and Wood's alloy bonding layer, Li2MCl4 solid electrolyte and tin-copper alloy bonding layer. When preparing bonding layers on the surfaces of different solid electrolytes, the metals contained in multiple bonding layers can be used as targets for co-sputtering, or a bonding layer alloy metal can be prepared into an alloy target for sputtering.

[0010] Preferably, the composition ratio of the tin-lead alloy is: Sn / Pb=x / (1-x), x=0.3~0.7, the composition ratio of the tin-silver-copper ternary alloy is: Sn / Ag / Cu=x / y / (1-xy), x=0~0.1, y=0~0.1, the composition ratio of the tin-silver alloy is: Sn / Ag=x / (1-x), x=0.3~0.7, the composition ratio of the tin-copper alloy is: Sn / Cu=x / (1-x), x=0.3~0.7, the composition ratio of the Wood's alloy is: Pb / Sn / Bi / Cd, (0~0.25) / (0~0.125) / (0~0.5) / (0~0.125).

[0011] The present invention also discloses an interface bonding method for lithium and a solid electrolyte, wherein the interface bonding method is used to prepare the above-mentioned interface bonding layer, and the interface bonding method comprises the following steps:

[0012] Step S1, removing impurities from the surface of the solid electrolyte matrix material and polishing it;

[0013] Step S2, using the bonding layer alloy as a target material, performing sputtering deposition on the solid electrolyte matrix material polished in step S1 to form an interface bonding layer;

[0014] Step S3, bonding the metal lithium negative electrode and the solid electrolyte with a bonding layer at 70-150° C. and a pressure of 50-200 MPa;

[0015] The sputtering conditions of the interface bonding method include: background vacuum degree 0.1×10 -4 ~9.9×10 -4 Pa, the working gas pressure is 0.30~0.55Pa, and the purity of the bonding layer alloy as the target material is ≥99.99%.

[0016] Preferably, the target distance of the interface bonding method is 8 to 12 cm, the sputtering power is 70 to 90 W, the sputtering temperature is 20 to 30° C., the sample tray transfer speed is 0.5 to 1 cm / s, and the sputtering time is 10 to 30 min.

[0017] Preferably, the target distance of the interface bonding method is 8 to 12 cm, the sputtering power is 70 to 90 W, the sputtering temperature is 20 to 30° C., the sample tray transfer speed is 0.5 to 1 cm / s, and the sputtering time is 10 to 30 min.

[0018] The present invention also discloses an application of an interface bonding layer between lithium and a solid electrolyte. The application adopts the above-mentioned interface bonding layer. The application includes using the interface bonding layer to prepare a lithium battery. The lithium battery includes: a solid-state lithium symmetrical battery and a solid-state lithium metal full battery.

[0019] Preferably, when the lithium battery is a solid-state lithium symmetrical battery, an interface bonding layer is deposited on both side surfaces of a solid electrolyte matrix material, and then the metal lithium negative electrode is bonded to both sides of the electrolyte by a hot pressing bonding method to prepare a solid-state lithium symmetrical battery in a battery shell.

[0020] Preferably, when the lithium battery is a solid-state lithium metal full battery, the interface bonding layer is deposited on both side surfaces of the solid electrolyte matrix material, and then the metal lithium negative electrode is bonded to one side of the electrolyte by a hot pressing bonding method, and the positive electrode material is matched on the other side.

[0021] The beneficial effects of the present invention are:

[0022] 1. The interfacial bonding method provided by the present invention has wide applicability. It is not only applicable to different types of solid electrolytes (such as NASICON type, garnet type, sulfide, halide), but can also be applied to the preparation of solid-state lithium batteries. The method of the present invention can adapt to various material systems and has strong adaptability.

[0023] 2. The present invention significantly improves the physical contact behavior of the interface between the solid electrolyte and metallic lithium by depositing a bonding layer on the surface of the solid electrolyte, and enhances the stability of the interface. The good solubility and alloying properties of the bonding layer and metallic lithium avoid electrochemical instability at the interface and reduce the interface impedance.

[0024] 3. The bonding layer of the present invention can induce uniform deposition of metallic lithium, avoiding disordered growth of lithium dendrites, thereby effectively reducing the risk of lithium dendrites piercing the solid electrolyte, preventing battery failure, and improving battery safety.

[0025] 4. The bonding layer of the present invention not only provides a strong interface connection, but also optimizes the conduction path of lithium ions and reduces the interface impedance. The present invention improves the ion conductivity of the battery, effectively improves the energy density and cycle life of the battery, and significantly improves the overall electrochemical performance.

[0026] 5. The magnetron sputtering method of the present invention is carried out in a vacuum environment, the process parameters are controllable, the thickness and uniformity of the bonding layer are easy to regulate, the preparation process is stable, the method of the present invention has mild conditions, the bonding temperature and pressure are moderate, and it is easy to implement in large-scale production.

[0027] 6. The thickness of the bonding layer of the present invention is optimized, which will neither increase the transmission resistance of lithium ions nor cause damage and failure of the battery during the cycle due to being too thin, thereby achieving the optimal interface enhancement effect. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the relevant technologies in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] This embodiment provides a universal method for bonding metal lithium to a solid electrolyte interface and a solid lithium battery application, including a solid electrolyte matrix and an interface bonding layer; the solid electrolyte is one of a NASICON-type oxide solid electrolyte, a garnet-type solid electrolyte, a sulfide solid electrolyte, and a halide solid electrolyte. The bonding layer composition is one of a tin-lead alloy, a tin-silver-copper ternary alloy, a tin-silver alloy, a tin-copper alloy, and a Wood's alloy. The bonding method is hot pressing bonding.

[0030] The metal lithium and solid electrolyte interface bonding method of the present invention shows significant advantages in the preparation of solid-state lithium symmetrical batteries and solid-state lithium metal full batteries. Through magnetron sputtering technology, a bonding layer is deposited on the surface of the solid electrolyte to form an effective interface bonding layer, which is mainly composed of materials such as tin-lead alloy and tin-silver-copper ternary alloy. The design of this bonding layer not only enhances the physical contact between the solid electrolyte and the metal lithium, reduces the interface impedance, but also induces the uniform deposition of lithium, thereby effectively inhibiting the formation of lithium dendrites. By optimizing the bonding process and the composition of the bonding layer, this method significantly improves the stability of the interface, reduces the performance degradation caused by the instability of the interface, and ultimately improves the energy density and cycle life of the battery. Its wide applicability enables this method to adapt to different types of solid electrolytes, providing strong support for the development of high-performance, safe and reliable solid-state lithium batteries in the future.

[0031] The specific preparation steps are as follows:

[0032] The solid electrolyte is fixed in the magnetron sputtering chamber and covered with a baffle. According to the predetermined bonding alloy elements, the corresponding target material (purity ≥ 99.99%) is selected. Before use, the target material is cleaned and dried with acetone. Subsequently, pre-sputtering is performed for 5 to 10 minutes to remove oxides and other impurities on the surface of the target material to ensure that the material deposited on the solid electrolyte during the subsequent sputtering process is pure and free of impurities. Then, the baffle of the sample tray is opened and sputtering is started. The process parameters of RF magnetron sputtering are set as follows: background vacuum (0.1 to 9.9) × 10 -4 Pa, working gas pressure is 0.30-0.55Pa, target distance is 8-12cm, sputtering power is 70-90W, sputtering temperature is 20-30℃, sample tray transfer speed is 0.5-1cm / s, and sputtering time is 10-30 minutes. According to different target materials, the optimized sputtering time, power and gas pressure are selected. Subsequently, a solid electrolyte sheet with a bonding layer uniformly attached to the surface is obtained, wherein the thickness of the bonding layer is about 0.5-5μm. Subsequently, the metal lithium negative electrode is attached to the solid electrolyte with a bonding layer, and hot-pressed bonding is performed at 70-150℃ and a pressure of 50-200MPa. The above bonding process is carried out in a drying room with a dew point of -50°.

[0033] The present invention uses the above-mentioned solid electrolyte to prepare a solid-state lithium symmetrical battery and a solid-state lithium metal full battery. (1) The preparation of the solid-state lithium symmetrical battery is to put the solid electrolyte with a metal lithium negative electrode bonded on both sides into a standard CR2032 button battery to assemble the solid-state symmetrical battery. (2) The preparation of the solid-state lithium metal full battery is to match the solid electrolyte with a metal lithium negative electrode bonded on one side with the positive electrode, put it into a standard CR2032 button battery, and assemble the solid-state lithium metal full battery.

[0034] Example

[0035] Example 1 provides a Sn / Ag alloy bonded Li 1.5 Al 0.5 Ti 1.5 (PO4)3 solid electrolyte and lithium metal method

[0036] The pre-prepared Li 1.5 Al 0.5 Ti 1.5 The (PO4)3 solid electrolyte sheet was placed in the sputtering chamber and covered with a baffle. The Sn / Ag target with a purity of 99.99% was cleaned and dried with acetone, and then pre-sputtered for 5 minutes to remove surface oxides and other impurities to ensure the pure Sn / Ag bonding layer deposited on the surface of the subsequent solid electrolyte. The process parameters of RF magnetron sputtering were: at a background vacuum of 5.0×10 -4 When the argon gas with a purity of 99.99% was introduced at 0.35Pa, the working pressure was 0.35Pa, the target distance was 10cm, the sputtering power was 70W, the sputtering temperature was 25℃, the sample plate transfer speed was 1cm / s, and the sputtering time was 20min. The Sn / Ag bonding layer modified Li 1.5 Al 0.5 Ti 1.5 (PO4)3 solid electrolyte. The bonding layer prepared in this embodiment is about 100nm. 1.5 Al 0.5 Ti 1.5 The (PO4)3 solid electrolyte was bonded at 150°C and a pressure of 150MPa.

[0037] Example 2 provides a Sn / Ag / Cu ternary alloy bonded Li7La3Zr2O 12 Solid electrolyte and lithium metal method

[0038] The pre-prepared Li7La3Zr2O 12 The solid electrolyte sheet was placed in the sputtering chamber and covered with a baffle. The Sn / Ag / Cu target with a purity of 99.99% was cleaned and dried with acetone, and then pre-sputtered for 5 minutes to remove surface oxides and other impurities to ensure the pure Sn / Ag / Cu bonding layer deposited on the surface of the subsequent solid electrolyte. The process parameters of RF magnetron sputtering were: at a background vacuum of 5.0×10 -4 When the argon gas with a purity of 99.99% was introduced at 1.5 Pa, the working pressure was 0.35 Pa, the target distance was 10 cm, the sputtering power was 75 W, the sputtering temperature was 25 ° C, the sample plate transfer speed was 1 cm / s, and the sputtering time was 30 min. Li7La3Zr2O modified with Sn / Ag / Cu bonding layer was prepared. 12Solid electrolyte. The bonding layer prepared in this embodiment is about 150nm. The metal lithium negative electrode is connected with the Li7La3Zr2O 12 The solid electrolyte was bonded at 120°C and a pressure of 130 MPa.

[0039] Example 3 provides a Sn / Pb alloy bonded Li5La3Nb2O 12 Solid electrolyte and lithium metal method

[0040] The pre-prepared Li5La3Nb2O 12 The solid electrolyte sheet was placed in the sputtering chamber and covered with a baffle. The Sn / Pb target with a purity of 99.99% was cleaned and dried with acetone, and then pre-sputtered for 5 minutes to remove surface oxides and other impurities to ensure the pure Sn / Pb bonding layer deposited on the surface of the subsequent solid electrolyte. The process parameters of RF magnetron sputtering were: at a background vacuum of 5.0×10 -4 When the argon gas with a purity of 99.99% was introduced at 0.35Pa, the working pressure was 0.35Pa, the target distance was 10cm, the sputtering power was 80W, the sputtering temperature was 25℃, the sample plate transfer speed was 0.5cm / s, and the sputtering time was 15min. Li5La3Nb2O modified with Sn / Pb bonding layer was prepared. 12 Solid electrolyte. The bonding layer prepared in this embodiment is about 120nm. The metal lithium negative electrode is connected with the Li5La3Nb2O 12 The solid electrolyte was bonded at 150°C and a pressure of 150 MPa.

[0041] Example 4 provides a method for bonding a Sn / Cu alloy to a Li3InCl6 solid electrolyte and metallic lithium

[0042] The prepared Li3InCl6 solid electrolyte sheet was placed in the sputtering chamber and covered with a baffle. The Sn / Cu target with a purity of 99.99% was cleaned and dried with acetone, and then pre-sputtered for 5 minutes to remove surface oxides and other impurities to ensure the pure Sn / Cu bonding layer deposited on the surface of the solid electrolyte. The process parameters of RF magnetron sputtering were as follows: at a background vacuum of 5.0×10 -4 Pa, argon gas with a purity of 99.99%, the working gas pressure is 0.35Pa, the target distance is 10cm, the sputtering power is 80W, the sputtering temperature is 25℃, the sample tray transfer speed is 1cm / s, and the sputtering time is 20min, and the Li3InCl6 solid electrolyte modified with the Sn / Cu bonding layer is prepared. The bonding layer prepared in this embodiment is about 150nm. The metal lithium negative electrode is bonded to the Li3InCl6 solid electrolyte with the Sn / Cu bonding layer at 170℃ and a pressure of 120MPa.

[0043] Example 5 provides a Pb / Sn / Sb / Cd alloy bonded Li 6.25 LqCy 1.75 Ta 0.25 O 12 Solid electrolyte and lithium metal method

[0044] The pre-prepared Li 6.25 LqCy 1.75 Ta 0.25 O 12 The solid electrolyte sheet was placed in the sputtering chamber and covered with a baffle. The Pb / Sn / Sb / Cd target with a purity of 99.99% was cleaned and dried with acetone, and then pre-sputtered for 5 minutes to remove surface oxides and other impurities to ensure the subsequent deposition of a pure Pb / Sn / Sb / Cd bonding layer on the surface of the solid electrolyte. The process parameters of the RF magnetron sputtering were: at a background vacuum of 5.0×10 -4 When the argon gas with a purity of 99.99% was introduced at 0.35Pa, the working pressure was 0.35Pa, the target distance was 10cm, the sputtering power was 70W, the sputtering temperature was 25℃, the sample plate transfer speed was 1cm / s, and the sputtering time was 20min. The Sn / Ag bonding layer modified Li 6.25 LqCy 1.75 Ta 0.25 O 12 Solid electrolyte. The bonding layer prepared in this embodiment is about 100nm. The metal lithium negative electrode is connected to the Li 6.25 LqCy 1.75 Ta 0.25 O 12 The solid electrolyte is bonded at 1100°C and a pressure of 200 MPa.

[0045] Example 6 provides a Sn / Pb alloy bonded Li 1.5 Al 0.5 Ge 1.5 (PO4)3 solid electrolyte and lithium metal method

[0046] The pre-prepared Li 1.5 Al 0.5 Ge 1.5 The (PO4)3 solid electrolyte sheet was placed in the sputtering chamber and covered with a baffle. The Sn / Pb target with a purity of 99.99% was cleaned and dried with acetone, and then pre-sputtered for 5 minutes to remove surface oxides and other impurities to ensure the pure Sn / Pb bonding layer deposited on the surface of the subsequent solid electrolyte. The process parameters of RF magnetron sputtering were: at a background vacuum of 5.0×10 -4When the argon gas with a purity of 99.99% was introduced at 0.30Pa, the working pressure was 0.30Pa, the target distance was 8cm, the sputtering power was 90W, the sputtering temperature was 25℃, the sample plate transfer speed was 1cm / s, and the sputtering time was 15min. The Sn / Pb bonding layer modified Li 1.5 Al 0.5 Ge 1.5 (PO4)3 solid electrolyte. The bonding layer prepared in this embodiment is about 90nm. 1.5 Al 0.5 Ge 1.5 The (PO4)3 solid electrolyte was bonded at 150°C and a pressure of 100 MPa.

[0047] Example 7 provides a method for bonding Li2ZrCl4 solid electrolyte and metallic lithium using Sn / Ag / Cu ternary alloy

[0048] The prepared Li2ZrCl4 solid electrolyte sheet was placed in the sputtering chamber and covered with a baffle. The Sn / Ag / Cu target with a purity of 99.99% was cleaned and dried with acetone, and then pre-sputtered for 5 minutes to remove surface oxides and other impurities to ensure the pure Sn / Ag / Cu bonding layer deposited on the surface of the subsequent solid electrolyte. The process parameters of RF magnetron sputtering were: at a background vacuum of 5.0×10 -4 When the argon gas with a purity of 99.99% is introduced at 0.30Pa, the working gas pressure is 0.30Pa, the target distance is 12cm, the sputtering power is 85W, the sputtering temperature is 25℃, the sample plate transfer speed is 0.5cm / s, and the sputtering time is 30min, and the Li2ZrCl4 solid electrolyte modified with the Sn / Ag / Cu bonding layer is prepared. The bonding layer prepared in this embodiment is about 150nm. The metal lithium negative electrode is bonded with the Li2ZrCl4 solid electrolyte with the Sn / Ag / Cu bonding layer at 150℃ and a pressure of 150MPa.

[0049] Table 1. Comparison of solid-state lithium symmetric battery performance between examples and control examples

[0050]

[0051] Table 2. Comparison of solid-state lithium full battery performance between examples and control examples

[0052]

[0053] Table 1 shows the performance comparison between Examples 1 to 7 and the control example, highlighting the advantages of solid-state lithium metal full batteries with bonding layers in multiple key parameters. At 30°C and a current density of 0.1 mA cm-2, the overpotentials of these batteries are all below 100 mV, indicating that the bonding layer significantly reduces the energy loss of the battery and improves the energy efficiency of the battery. In addition, the interface impedance is less than 100 Ω / cm 2 , further proving that the bonding layer optimizes the contact between the electrolyte and lithium metal and improves ionic conductivity. This low impedance state is a key factor in ensuring high battery efficiency. Table 2 further shows the performance under higher rate conditions. At 30°C and 0.2C rate, the solid-state metal lithium full battery with a bonding layer, the cobalt nickel manganese oxide / lithium metal battery showed good cycling performance and high capacity retention. After a long period of cycle testing, the discharge capacity of these batteries remained at a high level, showing that the introduction of the bonding layer effectively enhanced the battery's cycling stability. Overall, these data show that the application of the bonding layer not only improves the battery's immediate performance, but also ensures its reliability in long-term use, providing strong support for the practical application of solid-state metal lithium batteries.

[0054] The introduction of the bonding layer significantly improves the performance of solid-state lithium metal batteries, which is mainly reflected in the following aspects: (1) Interface stability: The bonding layer effectively enhances the physical contact between the solid electrolyte and lithium metal, reduces interface instability, and reduces the occurrence of interface reactions. (2) Reduced interface impedance: The presence of the bonding layer reduces the interface impedance of the battery, improves ionic conductivity, and enables lithium ions to migrate more quickly, thereby increasing the power density of the battery. (3) Uniform lithium deposition: The bonding layer helps to induce uniform deposition of lithium metal, inhibits the formation of lithium dendrites, reduces the risk of damage to the solid electrolyte, and extends the service life of the battery. (4) Extended cycle life: The optimized design and modification technology of the bonding layer improve the overall cycle stability of the battery, allowing it to maintain higher performance during multiple charge and discharge cycles. In summary, the introduction of the bonding layer not only improves the safety and stability of solid-state lithium metal batteries, but also significantly improves the electrochemical performance, laying the foundation for its commercial application.

[0055] The ultimate goal of the present invention is to improve the interfacial contact between the solid electrolyte and the lithium negative electrode while avoiding the interfacial instability behavior between the solid electrolyte and the metallic lithium from the root, avoiding the irreversible consumption of active lithium and the solid electrolyte, and thus avoiding the capacity loss and early failure of the solid-state battery caused by the penetration of the dendrites into the solid electrolyte. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concepts. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these changes and variations.

[0056] In summary, the present invention fundamentally avoids the interface instability behavior between the solid electrolyte and metallic lithium, avoids the irreversible consumption of active lithium and solid electrolyte, and further avoids the capacity loss and early failure of the solid-state battery caused by dendrites penetrating the solid electrolyte. Therefore, the present invention has broad application prospects in the field of energy storage material technology.

[0057] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. An interfacial bonding layer between lithium and a solid electrolyte, characterized in that: The interface bonding layer is a bonding layer formed by depositing a bonding layer alloy on the surface of a solid electrolyte matrix material by radio frequency magnetic sputtering; The bonding layer alloy includes: tin-lead alloy, tin-silver-copper ternary alloy, tin-silver alloy, tin-copper alloy, Wood's alloy; the solid electrolyte includes: NASICON type oxide solid electrolyte, garnet type solid electrolyte, sulfide solid electrolyte, halide solid electrolyte; The thickness of the interface bonding layer is 0.5-5 μm.

2. The interfacial bonding layer of lithium and solid electrolyte according to claim 1, characterized in that: The NASICON-type solid electrolyte comprises: Li 1+x Al x Ti 2-x (PO4)3(x=0.3~0.5) and Li 1+x Al x Ge 2-x (PO4)3(x=0.3-0.5); the garnet-type solid electrolyte includes: Li7La3Zr2O 12 , Li 3+x La 2 / 3-x TiO3, Li5La3Nb2O 12 and Li 6.25 LqCy 1.75 Ta 0.25 O 12 ; The sulfide solid electrolyte includes: Li2S-P2S5, Li 10 GeP2S 12 ,Li7P3S 11 and Li2S-Sb2S3; the halide solid electrolyte includes: Li3MX6 (M=Y, Er, Sc, In, X=F, Cl, Br) and Li2MCl6 (M=Zr, Cd, Ti).

3. The interfacial bonding layer of lithium and solid electrolyte according to claim 2, characterized in that: The combination of the interface bonding layer includes: a combination of Li1+xAlxTi2-x(PO4)3 solid electrolyte and a tin-lead alloy bonding layer, a combination of Li7La3Zr2O12 solid electrolyte and a tin-silver-copper ternary alloy bonding layer, a combination of Li2S-P2S5 solid electrolyte and a tin-lead alloy bonding layer, a combination of Li3MX6 solid electrolyte and a Wood's alloy bonding layer, and a Li2MCl4 solid electrolyte and a tin-copper alloy bonding layer.

4. The interfacial bonding layer of lithium and solid electrolyte according to claim 1, characterized in that: The composition ratio of the tin-lead alloy is: Sn / Pb=x / (1-x), x=0.3~0.7, the composition ratio of the tin-silver-copper ternary alloy is: Sn / Ag / Cu=x / y / (1-xy), x=0~0.1, y=0~0.1, the composition ratio of the tin-silver alloy is: Sn / Ag=x / (1-x), x=0.3~0.7, the composition ratio of the tin-copper alloy is: Sn / Cu=x / (1-x), x=0.3~0.7, the composition ratio of the Wood's alloy is: Pb / Sn / Bi / Cd, (0~0.25) / (0~0.125) / (0~0.5) / (0~0.125).

5. A method for interfacial bonding of lithium and a solid electrolyte, characterized in that: The interface bonding method is used to prepare the interface bonding layer according to any one of claims 1 to 4, and the interface bonding method comprises the following steps: Step S1, removing impurities from the surface of the solid electrolyte matrix material and polishing it; Step S2, using the bonding layer alloy as a target material, performing sputtering deposition on the solid electrolyte matrix material polished in step S1 to form an interface bonding layer; Step S3, bonding the metal lithium negative electrode and the solid electrolyte with a bonding layer at 70-150° C. and a pressure of 50-200 MPa; The sputtering conditions of the interface bonding method include: background vacuum degree of 0.1×10-4 to 9.9×10-4 Pa, working gas pressure of 0.30 to 0.55 Pa, and purity of the bonding layer alloy as a target material of ≥99.99%.

6. The method for interfacial bonding of lithium and solid electrolyte according to claim 5, characterized in that: The target distance of the interface bonding method is 8-12 cm, the sputtering power is 70-90 W, the sputtering temperature is 20-30° C., the sample plate transmission speed is 0.5-1 cm / s, and the sputtering time is 10-30 min.

7. The method for interfacial bonding of lithium and solid electrolyte according to claim 5, characterized in that: The target distance of the interface bonding method is 8-12 cm, the sputtering power is 70-90 W, the sputtering temperature is 20-30° C., the sample plate transmission speed is 0.5-1 cm / s, and the sputtering time is 10-30 min.

8. An application of a lithium and solid electrolyte interface bonding layer, characterized in that: The application adopts the interface bonding layer described in any one of claims 1 to 4, and the application includes using the interface bonding layer to prepare a lithium battery, and the lithium battery includes: a solid-state lithium symmetric battery and a solid-state lithium metal full battery.

9. The use of a lithium and solid electrolyte interface bonding layer according to claim 8, characterized in that: When the lithium battery is a solid-state lithium symmetrical battery, an interface bonding layer is deposited on both sides of the solid electrolyte matrix material, and then the metal lithium negative electrode is bonded to both sides of the electrolyte by a hot pressing bonding method to prepare a solid-state lithium symmetrical battery in a battery shell.

10. The use of a lithium and solid electrolyte interface bonding layer according to claim 8, characterized in that: When the lithium battery is a solid-state lithium metal full battery, the interface bonding layer is deposited on both sides of the solid electrolyte matrix material, and then the metal lithium negative electrode is bonded to one side of the electrolyte by a hot pressing bonding method, and the positive electrode material is matched on the other side.

Citation Information

Patent Citations

  • Solid-state lithium ion battery and preparation method thereof

    CN111193062A

  • Composite negative electrode, solid-state lithium battery and preparation method of solid-state lithium battery

    CN112420978A

  • All-solid-state thick film lithium battery with alloy interface-lithium thick film structure and preparation method of all-solid-state thick film lithium battery

    CN114865099A

  • Lithium battery thermal runaway suppression assembly and application thereof

    CN115732773A

  • Phase conversion alloy negative electrode and solid-state battery thereof

    CN118472230A

Cited By

  • Low-melting-point iodide modified lithium composite LATP solid electrolyte and preparation method and application thereof

    CN122494784A